USAGE AND IMPACT OF E-RESOURCES IN DIGITAL ERA: SPECIAL REFERENCE TO PHARMACY COLLEGES OF TUMKUR CITY, KARNATAKA (International Journal of Food and Nutritional Sciences, 2023)
This research study investigates the utilization and impact of e-resources among users in pharmacy colleges located in Tumkur City, Karnataka State. The study aims to examine the extent of e-resource usage, explore the purposes for which e-resources are employed, and assess the satisfaction levels associated with their utilization. A quantitative research design was employed, and a total of 180 participants, including 124 faculty members and 1161 students from ten pharmacy colleges were selected. Data collection was carried out through a questionnaire distributed to potential participants, with 180 respondents providing valuable insights. .